Including transcultural nursing content in the curriculum - Part 2 - L. de Villiers; D. van der Wal (AOSIS, 1995)
Transcultural nursing should be included in the curricula of the basic nursing courses. In this article, the transcultural nursing curriculum content that could be included, is discussed. To ensure a comprehensive approach to this field, a basic course in socio-cultural anthropology should be followed by transcultural nursing study units at strategic points in the curriculum.